2014
DOI: 10.1186/1472-6882-14-199
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of Mangifera indica L. kernel extract on human breast cancer (MCF-7 and MDA-MB-231 cell lines) and bioactive constituents in the crude extract

Abstract: BackgroundWaterlily Mango (Mangifera indica L.) is thought to be antioxidant-rich, conferred by its functional phytochemicals.MethodsThe potential anticancer effects of the ethanolic kernel extract on breast cancer cells (MDA-MB-231 and MCF-7) using MTT, anti-proliferation, neutral red (NR) uptake and lactate dehydrogenase (LDH) release assays were evaluated. Cytological studies on the breast cancer cells were also conducted, and phytochemical analyses of the extract were carried out to determine the likely bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 24 publications
9
90
0
2
Order By: Relevance
“…Our results are in well agreements with the previous studies where the exposures of various natural products have been shown to induced significant cytotoxic effects against different cancer cell lines (Srividya et al, 2012;Al-Oqail et al, 2013Al-Sheddi et al, 2014;Farshori et al, 2014). Our results also correlate with previous findings showing the in vitro cytotoxicity in this concentration range (Abdullah et al, 2014). Other plant extracts have also been shown to induce cytotoxicity against human lung adenocarcinoma cell line, A-549 (Solowey et al, 2014;Manglani et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in well agreements with the previous studies where the exposures of various natural products have been shown to induced significant cytotoxic effects against different cancer cell lines (Srividya et al, 2012;Al-Oqail et al, 2013Al-Sheddi et al, 2014;Farshori et al, 2014). Our results also correlate with previous findings showing the in vitro cytotoxicity in this concentration range (Abdullah et al, 2014). Other plant extracts have also been shown to induce cytotoxicity against human lung adenocarcinoma cell line, A-549 (Solowey et al, 2014;Manglani et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Vernodalin isolated from Centratherum anthelminticum seeds inhibits cell growth of MCF-7 and MDA-MB-231 by induction of cell cycle arrest and apoptosis, increased of reactive oxygen species (ROS) production coupled with a downregulation of antiapoptotic molecules (Bcl-2 and Bcl-xL) led to reduction of mitochondrial membrane potential and the release of cytochrome c from mitochondria to cytosol which triggered activation of caspase cascade, PARP cleavage, DNA damage and eventually cell death. These plants contain other chemicals that are not isolated but rather suspected to be the principal agent for the anticancer activities these are apigenin, apigenin glycosides, luteolin, luteolin-7 glucosides, p-coumarin, lupeol, lectins, naringin, nodifloretin, β silosterol, mangiferonic acid, pellitorine, kaempferol [38], curcumin, curcuminoids, a-turmerone, [33,37,39,40], quercetin [41,42], catechin, rutin [43], xanthorrhizol [40], mangiferin [44], ferric thiocyanate, thiobarbituric acid, isoquercetin, astragalin [45], damnacanthal [46], naphthoquinones [47], triterpenoids, flavonoids, gallic acid, gingerol [48] anonaine, isolaureline, annonamine [49], xanthones [50], flavonoids, stigmasterol, carotenoids, and ascorbic acid [51], among which many are reported for their cytotoxicity and chemopreventive activity against breast cancer cell that are promising anticancer agents and has been adapted for alternative cancer therapies. Many studied plants were shown to possess variable chemical compounds that possess a tumor suppressive activities and associated with potent anticancer responses, [37,40,44,[51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxic potential of CE is lower than other plant extracts such as Mangifera indica kernel (15 μg/ml), Elephantopus scaber (14,69 μg/ml) and Dillenia suffruticosa (76 μg/ml) [14][15][16]. However CE is stronger than Argyreia nervosa leaf (>2500 μg/ml), Dypterocarpus turbinatus leaf (>2500 μl/ml), and Saraca asoca leaf (>2500 μg/ml) [17].…”
Section: Modulation Of Catechin and Caffeine Concentration Affected Cmentioning
confidence: 99%